A High Density Genetic Map Derived from RAD Sequencing and Its Application in QTL Analysis of Yield-Related Traits in Vigna unguiculata - Pan, Lei; Wang, Nian; Wu, Zhihua; Guo, Rui; Yu, Xiaolu; Zheng, Yu; Xia, Qiuju; Gui, Songtao; Chen, Chanyou (Frontiers in Plant Science, 2017)
Cowpea [Vigna unguiculata（L.）Walp.], spread widely in the semi-arid tropics, is an annual legume of economic importance. However, high-density genetic maps of cowpea are still in lack. Here, we identified 34,868 SNPs (single nucleotide polymorphisms) that were evenly distributed in the cowpea genome based on the RAD sequencing (restriction-site associated DNA sequencing) technique. Of these SNPs, 17,996 reliable SNPs were allotted to 11 consensus linkage groups (LGs) and were used for genotyping. The length of the genetic map was 1,194.25 cM in total with a mean distance of 0.066 cM/interval locus. The map quality and synteny were compared with the common bean (Phaseolus vulgaris) and the previous cowpea SNP genetic map. Using this map and the F2:3 population, combined with the CIM (composite interval mapping) method, eleven QTLs of yield-related trait were detected on seven LGs (LG4, 5, 6, 7, 9, 10 and 11) in cowpea. These QTLs explained 0.05~17.32% of the total phenotypic variation. Among these, four QTLs were for PL (pod length), four QTLs for TGW (thousand-grain weight), two QTLs for GN (grain number per pod), and one QTL for CL (carpopodium length). Our results will provide a foundation for understanding genes in the cowpea and genus Vigna.